2013
DOI: 10.3389/fnhum.2013.00510
|View full text |Cite
|
Sign up to set email alerts
|

The sensory channel of presentation alters subjective ratings and autonomic responses toward disgusting stimuli—Blood pressure, heart rate and skin conductance in response to visual, auditory, haptic and olfactory presented disgusting stimuli

Abstract: Disgust causes specific reaction patterns, observable in mimic responses and body reactions. Most research on disgust deals with visual stimuli. However, pictures may cause another disgust experience than sounds, odors, or tactile stimuli. Therefore, disgust experience evoked by four different sensory channels was compared. A total of 119 participants received 3 different disgusting and one control stimulus, each presented through the visual, auditory, tactile, and olfactory channel. Ratings of evoked disgust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
61
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 38 publications
4
61
0
3
Order By: Relevance
“…One hypothesis might refer to idiosyncratic properties of each physiological measure leading to greater sensitivity for one or the other modality: e.g., galvanic responses might be more sensitive to the affective load of thermal stimuli. This possibility accords with previous evidence showing that events from different sensory channels trigger distinct physiological responses, including pain 43 and disgust 44 . Alternatively, SCRs might be more closely related to arousal or emotion dimensions associated with pain (but not disgust), independent from the effects of unpleasantness, as suggested by a recent meta-analysis which proposed that the autonomic system may generate a set of multiple responses that differ in across the basic emotions 45 .…”
Section: Discussionsupporting
confidence: 92%
“…One hypothesis might refer to idiosyncratic properties of each physiological measure leading to greater sensitivity for one or the other modality: e.g., galvanic responses might be more sensitive to the affective load of thermal stimuli. This possibility accords with previous evidence showing that events from different sensory channels trigger distinct physiological responses, including pain 43 and disgust 44 . Alternatively, SCRs might be more closely related to arousal or emotion dimensions associated with pain (but not disgust), independent from the effects of unpleasantness, as suggested by a recent meta-analysis which proposed that the autonomic system may generate a set of multiple responses that differ in across the basic emotions 45 .…”
Section: Discussionsupporting
confidence: 92%
“…The insula supports the integration of this information and thus seems to contribute essentially to the feeling of disgust. Accordingly, Croy et al ( 2013 ) showed that disgust could be evoked via visual, auditory, tactile, and olfactory stimulation. Peripheral responses such as blood pressure, heart rate, or galvanic skin response, however, varied with modality.…”
mentioning
confidence: 99%
“…Thus, hair, a tangible cue, is more easily perceived as a contamination cue. Second, greater disgust toward hair on a product may stem from the visual perception of a bodily substance (Croy et al, ) that appears to be a violent invasion of territory (Rozin et al, ). Consequently, in an attempt to defend themselves, individuals withdraw from the disgust‐eliciting source and strongly reject the contaminated object, thereby expressing higher disgust, which consequently decreases product evaluation.…”
Section: Discussionmentioning
confidence: 99%